Scoliosis Curvature Follows Thoracic Organ Orientation. Issue 6 (15th March 2020) - Compton, Jocelyn; Voort, Wyatt Vander; Weinstein, Stuart
Abstract : Study Design: Retrospective cohort study, Level of Evidence III. Objective: To determine the relationship between internal organ orientation and adolescent idiopathic scoliosis (AIS) convexity directionality. Summary of Background Data: AIS affects 2% to 3% of the general population and demonstrations 80% to 99% right thoracic curve convexity. The mechanism of AIS as well as explanation for right-sided predominance is largely unknown. Methods: A retrospective chart review of all patients with dextrocardia from 2008 to 2018 was performed at a single institution. Upright chest x-rays and scoliosis x-rays were evaluated for scoliosis by measurement of Cobb angle. Chart review was performed to extract age, advanced imaging results, and surgical intervention. Results: Of 110 patients identified with dextrocardia, 19 patients exhibited radiographic features consistent with AIS (Cobb angle >10°). Fifteen (79%) of these patients demonstrated left-sided thoracic curvature. Six patients showed isolated dextrocardia with normal abdominal organ orientation; five patients (83%) showed left-sided thoracic curvature. There was not a statistical difference with regards to sex or curve severity. Magnetic resonance imaging (MRI) was performed on five patients with left-sided curvature without evidence of intra-spinal pathology. Conclusion: Dextrocardia shows increased incidence of AIS in both male and female patients. Left-sided thoracic curvature in cases with concurrent dextrocardia may not be associated with intra-spinal pathology as seen in the general population. These data suggest that thoracic organ orientation affects AIS convexity directionality. Level of Evidence: 3